Qualidade fisiológica de sementes de milho doce classificadas pela espessura e largura - Zucareli, Claudemir; Brzezinski, Cristian Rafael; Guiscem, Josiane Marlle; Henning, Fernando Augusto; Nakagawa, João [UNESP] (Escola de Agronomia e Engenharia de Alimentos/UFG, 2014)
Sweet maize seeds present lower physiologic quality, when compared to regular maize seeds, due to the influence of several features, such as the seed size and shape. Thus, this study aimed at evaluating the seed physiologic quality of two sweet maize cultivars (BR-401 and BR-402), separately classified according to thickness, by using slotted screen sieves (8/64 x 3/4, 9/64 x 3/4, 10/64 x 3/4, 11/64 x 3/4, 12/64 x 3/4 and 13/64 x 3/4), and width, with round screen sieves (17/64, 18/64, 19/64, 20/64, 21/64 and 22/64). For each cultivar, sorted lots were compared with the unrated batch, following a completely randomized design, in a 2x7 factorial scheme, with four replications. The biometric parameters evaluated were sieve retention, 100 seeds weight and water content. The physiologic quality was determined according to the first counting, germination, cold test, accelerated aging, electric conductivity and seedling emergence in the field. The classification with sieves improved the physiologic quality of sweet maize seeds. Seeds with intermediate thickness, for both cultivars, generally presented greater vigor. Concerning width, larger seeds, for the BR-401 cultivar, and intermediate seeds, for the BR-402 cultivar, showed better physiologic quality.

As sementes de milho doce apresentam qualidade fisiológica inferior à das sementes de milho comum, devido à influência de várias características, como o tamanho e a forma das sementes. Diante disto, este estudo objetivou avaliar a qualidade fisiológica de sementes de duas cultivares de milho doce (BR-401 e BR-402), classificadas, separadamente, quanto à espessura, por meio de peneiras de crivos oblongos (8/64 x 3/4, 9/64 x 3/4, 10/64 x 3/4, 11/64 x 3/4, 12/64 x 3/4 e 13/64 x 3/4), e quanto à largura, em peneiras de crivos redondos (17/64, 18/64, 19/64, 20/64, 21/64 e 22/64). Para cada cultivar, os lotes classificados foram comparados com o lote sem classificação, seguindo delineamento inteiramente casualizado, em esquema fatorial 2x7, com quatro repetições. Os parâmetros biométricos avaliados foram: retenção em peneira, massa de 100 sementes e teor de água. A qualidade fisiológica foi determinada por meio da primeira contagem, germinação, teste de frio, envelhecimento acelerado, condutividade elétrica e emergência de plântulas no campo. A classificação em peneiras melhorou a qualidade fisiológica das sementes de milho doce. As sementes com espessura intermediária, para ambas as cultivares, em geral, apresentaram maior vigor. Quanto à largura, sementes maiores, para a cultivar BR-401, e de largura intermediária, para a cultivar BR-402, apresentaram melhor qualidade fisiológica.
Physiologic quality of sweet maize seeds according to thickness and width
Keywords: Zea mays L.; classificação de sementes; germinação; emergência de plântulas; Zea mays L.; seed classification; germination; seedling emergence